Plan de negocios para la creación de una empresa de servicios de entregas a domicilio delivery en el cantón Durán - Arellano Daquilema, Ronny Michael (2021)
The present work reflects the analysis and evaluation of a business proposal to implement the creation of a company that offers home delivery service (Delivery) in the Durán canton belonging to the Guayas Province, a field research was carried out and descriptive research was also applied to establish a relationship with the people under study, In order to know in depth their way of behavior and to know what criteria the selected segment uses when choosing the Delivery service, we proceeded to use the techniques of interview and surveys, with the purpose that the Delivery service (TelollevoDurán), aims to meet the needs of customers, to provide immediate service and under the standards of hygiene that currently exists in the country..........